Rethinking Diet to Aid Human–Microbe Symbiosis - Derrien, Muriel; Veiga, Patrick (Trends in microbiology (Regular ed.), 2017)
The spread of the Western lifestyle has been accompanied by microbial changes thought to underlie the emergence of chronic, nontransmissible, immune-related diseases. The past decade has seen the unprecedented development of therapies for ‘replenishing’ the microbiota of sick individuals. However, functional and ecological solutions helping the host and the gut microbiota to cope with the ecological stressors of modern life are still lacking. In this review, we discuss how recent advances in gut microbiome science are leading to the identification of microbe-derived and health-relevant metabolites. These molecules will guide the selection of the next-generation of probiotics and dietary recommendations, which should also take the resident gut microbiota into account, to optimise efficacy. These solutions for maintaining a well-functioning gut ecosystem and promoting good health should be customised, palatable, and as widely accessible as possible. Diet is a key lever for microbiota-targeting strategies. The gut microbiota is a source of numerous bioactive molecules. Opportunities exist for the development of preventive strategies for host–microbe dysbiosis. The knowledge of a subject's microbiota can help to optimise dietary intervention. Diet customisation is a prerequisite for maximal beneficial effects. Next-generation probiotics should be selected for their ability to complement gut microbiome deficiencies.